Periferias urbanas en disputas y modelos divergentes de producción de ciudad. El conflicto por la tierra en Guernica, Provincia de Buenos Aires (Papeles, 2021)
The aim of this work is to analyze the tension and the dispute over land in the peri-urban space of the Buenos Aires Metropolitan Area (AMBA) between, on the one hand, the advance of gated communities and, on the other, popular urbanization through informal settlements. In the first place, we present a conceptual framework about peri-urban spaces and dispersed, fragmented and segregated urbanization. Then, we describe the recent evolution of those socio-housing modalities at the metropolitan level, highlighting the impact of the construction of the Presidente Perón Highway on the southern zone. The territorial conflict developed in Guernica (municipality of Presidente Perón) during 2020 is taken as a case, where more than two thousand families fought for access to land and housing through a process of “land recovery”, part of the which were claimed by a real estate developer for the construction of a complex of gated communities. Finally, we present the main characteristics of the urbanization project prepared by the Guernica Land Recovery Planning Commission, based on the instruments of provincial law 14.449 on Fair Access to Habitat, which could have been applied to face a peaceful solution to the conflict.
Keywords: urban expansion; gated communities; informal settlements; residential segregation; Guernica land recovery process.